Pattern of medication use among elderly patients attending medicine department in a tertiary care hospital in India - B, Swathi; BHAVIKA D (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The present study was aimed to assess the drug prescribing pattern and analyze the prescribing pattern using Beers criteria among elderly patients aged over 60 years Materials and Methods: The present study was a prospective observational study conducted in the outpatient department of general medicine in a tertiary care hospital for the duration of three months. Institutional ethics committee approval was taken prior to initiation of the study. Written informed consent was taken from each study subject. A total of 287 subjects who were aged more than 60 years recruited into the study. The data was collected in a pre structured case record form. Subjects’ demographic details, medical conditions and drugs included in prescription their dose; frequency and duration were noted in case record form. Results: Among 287 subjects 91.64% subjects belonged to 61-70years age group, remaining 8.36% subjects were >71year older and 57.14% were males and 42.86% were females. Hypertension was the most common cause of attending hospital followed by diabetes mellitus, CNS disorders, respiratory, cardiovascular disorders other than hypertension and infectious diseases. A total of 1574 formulations containing 1669 active ingredients and 90 FDCs were prescribed. And only 152 formulations were prescribed from outside hospital formulary. The average number of drugs per prescription was 5.48Â±2.00. Among the individual drugs vitamin B complex was the most commonly prescribed drug Conclusion: Â There is need for more rational prescribing and to form guidelines for safe and effective use of medicines in elderly patients.